Menelusuri Akar Perilaku Bullying di Sekolah: Kajian Sistematis Literatur Review (SLR) - Aly, Muhammad Fakhry; Firdaus, Rifqi (Jurnal Konseling dan Psikologi Indonesia, 2025)
This study aims to analyze bullying behavior in elementary schools using a systematic literature review (SLR) approach. Literature searches were conducted through Google Scholar with the help of the publish or perish application, using the keyword “bullying behavior in schools” and limiting articles published between 2019 and 2024. The results of this literature study identified various factors that influence bullying, including individual, family, school, and social media factors. Several studies also highlight the importance of self-efficacy in bullying victims, as well as the role of character education and moral values ​​in preventing bullying. An integrated and collaborative approach between parents, teachers, and the school community has proven effective in creating a safe environment for students. These findings provide important insights for the development of bullying prevention policies in elementary schools and the handling of the psychological impacts caused by bullying behavior.